Implementation of E-commerce in Denpasar City SMEs - Putu Wenny Saitri; Gde Bagus Brahma Putra; Made Ika Prastyadewi; Ni Putu Lisa Ernawatiningsih (Khazanah Sosial, 2024)
As a provincial capital that depends on tourism, the development of Denpasar City’s SMEs, especially in the tourism support sector, is growing rapidly. Coupled with technological advances, the development of SMEs must be able to adapt, one of which is by implementing e-commerce. This research aims to 1) explore the e-commerce needs of SMEs in Denpasar City and 2) analyze the factors that influence the use of e-commerce among SMEs in Denpasar City. The research was conducted on SMEs in Denpasar City with 140 respondents. A mixed-method approach was used to answer the research objectives. The research results show that e-commerce is a marketing medium for Denpasar City SMEs, primarily through Shopee and TikTok. Analysis using Atlas.ti indicates that human resources are still the main obstacle to implementing e-commerce in Denpasar City. Related to the factors that influence the decision to implement e-commerce, business duration, income, knowledge, technology, and product type are variables that significantly influence the implementation of e-commerce in Denpasar City. These results can be a reference regarding increasing SMEs’ capacity, especially regarding human resources and capital. Training, mentoring, and access to capital can raise SMEs’ awareness of the importance of technology in promoting and selling goods and services to increase income, which will lead to empowerment and prosperity.